1998
DOI: 10.1016/s0022-2275(20)33310-1
|View full text |Cite
|
Sign up to set email alerts
|

Membrane transport of long-chain fatty acids: evidence for a facilitated process

Abstract: In mammalian cells, membrane uptake of longchain fatty acids is mediated by two separate components; a passive component that is a linear function of the concentration of free fatty acid in the extracellular medium and a saturable component that exhibits the characteristics of a protein-facilitated process. This review summarizes the body of work that has accumulated related to the mechanism of fatty acid transport. Evidence in support of a facilitated uptake process is presented with relation to the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(27 citation statements)
references
References 100 publications
(118 reference statements)
0
27
0
Order By: Relevance
“…Thus, the most parsimonious explanation for impaired NEFA oxidation in aging is a block in mitochondrial β‐oxidation. Additional factors affecting NEFA oxidation include fatty acid translocase CD36 regulated cellular entry of NEFA (Abumrad et al ., ; Febbraio et al ., ) and regulation by PPARα and PGC1α. Hepatic Cd36 transcripts were lower in O‐CON mice (with higher hepatic fat) and higher in O‐RX mice (with lower hepatic fat).…”
Section: Discussionmentioning
confidence: 98%
“…Thus, the most parsimonious explanation for impaired NEFA oxidation in aging is a block in mitochondrial β‐oxidation. Additional factors affecting NEFA oxidation include fatty acid translocase CD36 regulated cellular entry of NEFA (Abumrad et al ., ; Febbraio et al ., ) and regulation by PPARα and PGC1α. Hepatic Cd36 transcripts were lower in O‐CON mice (with higher hepatic fat) and higher in O‐RX mice (with lower hepatic fat).…”
Section: Discussionmentioning
confidence: 98%
“…Unlike the vascular wall, where the overexpression of scavenger receptors favors the atherosclerotic process, in nonvascular cells of distant tissues it could help lower plasma lipids, as CD36/FAT mediates the uptake of long-chain fatty acids [ 144 , 145 ]. However, although several independent studies have reported reduced lipid levels in the plasma of transgenic mice overexpressing CD36 [ 37 , 146 , 147 , 148 , 149 , 150 , 151 ], a larger analysis clearly suggests that CD36 and oxLDLs form a pathogenic pair in different tissues.…”
Section: The Oxldl Signalingmentioning
confidence: 99%
“…Additional arguments for existence of receptor mediated NEFA uptake are based on experimental evidence. Studies of long chain FA uptake kinetics in intact cells [77,78], reviewed in [74,79,80], documented saturation of uptake at <10 nM unbound FA with competitive inhibition between different FAs [77] and suggested receptor-mediated uptake for FAs with hydrocarbon chains of more than 8 carbons. Similar conclusions were reached in a study of FA transfer using real time fluorescence microscopy that tested FA transfer inhibitors and long versus short chain FAs [81].…”
Section: Cellular Uptake Of Fatty Acidsmentioning
confidence: 99%